Investigation of the removal kinetics, thermodynamics and adsorption mechanism of anionic textile dye, Remazol Red RB, with powder pumice, a sustainable adsorbent from waste water - Gürses, Ahmet; Güneş, Kübra; Şahin, Elif; Açıkyıldız, Metin (Frontiers in Chemistry, 2023)
Excessive growth and abnormal use of dyes and water in the textile industry cause serious environmental problems, especially with excessive pollution of water bodies. Adsorption is an attractive, feasible, low-cost, highly efficient and sustainable technique in terms of green chemistry for the removal of pollutants from water. This study aims to investigate the removal kinetics, thermodynamics and adsorption mechanism of Remazol Red RB, which was chosen as a representative anionic reactive dye, from synthetic wastewater using powdered pumice, taking into account various experimental parameters such as initial dye concentration, adsorption time, temperature and pH. In order to elucidate the adsorption mechanism of Remazol Red RB on the powder pumice surface, electro kinetic and static contact angle measurements of the obtained samples for various initial dye concentrations under certain conditions, as well as the Fourier transform infrared spectrophotometer (FTIR) spectra before and after adsorption, X-ray powder diffraction. (XRD) diffractograms and High resolution transmission electron microscopy (HRTEM) images were used. Obtained results show that powder pumice is very suitable for high efficiency removal of anionic dye, and it is very effective in mild conditions in a period of 30-60 minutes. The experimental data showed a high agreement with the pseudo-second-order kinetic model and the Freundlich adsorption isotherm equation. In addition, thermodynamically, the process exhibited exothermic nature and standard isosteric enthalpy and entropy changes of -4.93kJ/mol.and 16.11 J/mol.K were calculated. It was determined that the adsorption mechanism was predominantly based on T-shaped pi-pi interactions and had physical characteristics